Structural Deficits and Bureaucratic Capacity in Tourism Implementation in Ende Regency: Defisit Struktural dan Kapasitas Birokrasi dalam Implementasi Pariwisata Kabupaten Ende - John Chrysostomus Sado; Eusabius Separera Niron; Bruno Rey Sonby Pantola (Jurnal Pemerintahan dan Politik, 2026)
Objective: This study analyzes the implementation of the Regional Tourism Development Master Plan (RIPPDA) in Ende Regency, focusing on how institutional and human resource capacity shape the effectiveness of tourism policy implementation. Design/Methodology/Approach: Using a descriptive qualitative approach, data were collected through in-depth interviews, documentation, and observation, with informants selected via purposive and snowball sampling. Data were analyzed using the Miles and Huberman interactive model, guided by George C. Edward III's implementation framework covering communication, resources, disposition, and bureaucratic structure. Findings: The study reveals structural deficits within the bureaucracy, weak cross-sectoral coordination, limited apparatus capacity, minimal budget support, and low adaptive and innovative disposition among implementers. These conditions push tourism policy implementation toward a merely administrative approach, hindering inclusive and sustainable tourism development. Practical Implications: Local governments need to strengthen bureaucratic capacity by improving human resource competency, restructuring institutions, enhancing cross-sectoral coordination, and reforming incentive and budgeting systems. A more inclusive and participatory communication strategy is also needed to engage communities in tourism development. Originality/Value: This research offers novelty by integrating institutional analysis and bureaucratic capacity to explain tourism policy implementation failure—an issue previously examined mainly from technical and economic perspectives. It contributes theoretically and empirically to understanding the link between structural deficits and policy effectiveness in regions with distinct socio-cultural characteristics, such as Ende Regency. Research Type: Research Paper